DISKURSUS PENDIDIKAN DAN PEREMPUAN DALAM KONSTRUKSI SOSIAL WARGA TAMIDUNG BATANG-BATANG SUMENEP - salama, salama (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2021)
This study aims to determine how social construction views education for women, forms of discrimination in viewing education for women, and the factors underlying the social construction that occurs in Tamidung Village. This research is a qualitative research, the approach used is a phenomenological approach. Data collection was carried out using several methods, namely observation, interviews, and documentation. This study uses Peter L Berger's social construction theory and Systems Theory as a form of analysis. The results show that the social construction of education for women can be explained in a dealectic that continues in three processes. Namely externalization (adjustment to the sociocultural world as a human product), objectivation (institutionalized social interaction in an intersubjective world or undergoing a process of institutionalization), internalization (the individual identifies himself in the social institutions in which the individual is a member). The social construct of education for women can be seen from several background factors, including early marriage, socio-culture, lack of awareness of the importance of education for women, the economic level of parents, and parental education. However, among the factors that most dominate the incidence of educational insignificance is early marriage. Keywords: Education, Women and Social Constructs